Flag and check: data access with monadically defined queries. - Rudolph, S; Krötzsch, M (ACM, 2013)
We introduce monadically defined queries (MODEQs) and nested monadically defined queries (NEMODEQs), two querying formalisms that extend conjunctive queries, conjunctive two-way regular path queries, and monadic Datalog queries. Both can be expressed as Datalog queries and in monadic second-order logic, yet they have a decidable query containment problem and favorable query answering complexities: a data complexity of P, and a combined complexity of NP (MODEQs) and PSpace (NEMODEQs). We show that (NE)MODEQ answering remains decidable in the presence of a well-known generic class of tuple-generating dependencies. In addition, techniques to rewrite queries under dependencies into (NE)MODEQs are introduced. Rewriting can be applied partially, and (NE)MODEQ answering is still decidable if the non-rewritable part of the TGDs permits decidable (NE)MODEQ answering on other grounds. Copyright 2013 ACM.